SENI CADAS DI WILAYAH BIAK TIMUR - Erlin Novita Idje Djami (BALAI ARKEOLOGI PAPUA, 2011)
Rock art in East Biak is an interesting subject to be examined. Its carved technique and motifs offer many important informations about cultural activities in the past, including the arts ’ benefits toward the society. This research will explore findings of rock art in East Biak in order to giving meanings or thorough description about the people and their culture in Biak. At least, there are five main motifs or objects which can be explored and revealed through the study: human, animal, vegetation, material culture and abstract or unidentified object. In addition to the understanding of rock art, the art can also contribute in learning human migration from Southeast Asia islands to Pacific region in the past since the art found widely in both area.